Meningkatkan Pemahaman Materi FPB dan KPK melalui Sistem Pembagi Bertangga pada Siswa Kelas VI SDN 125/IX Simpang Selat - R Rusnah (Jurnal Gentala Pendidikan Dasar, 2016)
This study aims to improve students' understanding of the biggest fellowship factor and the smallest multiple of alliances material by using a neighboring divider system in SDN 125 / IX Strait intersection. This type of research is Class Action Research. The method used is tests and observations. Based on the results of research and data analysis, it can be concluded that using a neighboring divider system can improve student learning outcomes on the subject of the biggest fellowship factor and the smallest multiple of alliances especially for Class VI SDN 125 / IX Simpang Selat Jambi Luar City District, Muaro Jambi Regency. This shows an increase in student learning outcomes with an average value in the first cycle with a value of 6.0 and in the second cycle with a value of 7.6.